(3CdaGX GdcaQs - (3nHrOQ GdnqQpTjO, eMeO Hf ESeGYjd Hf eMehO Hf eMeO, (B768 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3aEf GdfGS deG aSOJ bdhHge aSO SGFQ HOfge haTG efge eG aTGef GdcPH hGdfejeI hGdJgGdc Ydi GdOfjhjI hLeY MWGegG hGHJgGLge HPNGQagG hbdI eHGdGJge HCeQ GdOjf heG jfaYge aj GdBNQI ef GdGMJjGW aj CeQ GdYHGOGJ (B...s
(3BNQgG (B:s
(3hdS ddfUGQi HGdcSfHLGJ bdfShI ShOGA eVQhHI ef GddHO hRfGQG ef GdUha hgh GdeNJGQ hCeG dHS GdfUQGfj GdYeGeI Ch RfGQ GdCHQSje aLaGA aj Mb Cgd GdESdGe hecSQI dbdhH GdeSdef adG jJQchf YdjgeG hdh cGf deSde Ce Ch CH JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\37s
(3cTa GdXfhf (B2\1396s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds